Gerakan Sosial Penghijauan Di Lereng Barat Gunung Wilis Oleh Masyarakat Di Kabupaten Madiun - Wuwuh Asrining Surasmi (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2018)
The potential of a nation is determined by various things, among others: the population,quality of human resources (HR), natural resources, moral, and mental of the nationitself. Indonesia is a country with great territory, natural resources, and humanresources. The quality of our environment is now apprehensive, because of thedestruction of forests, forest fires, landslides, deforestation. It needs a social movementwith all components of society to create healthy living environment, green forest,greening on the western slopes of G.Wilis Madiun Regency . Madiun Regency has alarge area, large natural resources and hutanlebat, but strangely regional economicpower is not as large as the area and natural resources like other areas. Currently,forest destruction on the G.Wilis slope is quite alarming, both within the forest andoutside the forest. Views of deforested forests, arid lands, landslide cliffs occureverywhere on the western slopes of Wilis mountain, Flora and fauna are damaged, thecontent of 02 (oxygen) is thinning. For that required social movement of all societystart, ulama ', umara', young generation, student, student, youth cadets, santri pondokpesantren, social organization, all citizen, TNI / Polri to preserve forest. This researchis a qualitative research, data collection through interview, deep observation,documentation, with data analysis through stages: Data Collection, Data Reduction,Display data, Conclution / Vervying. The results show that there has been forestdestruction on the western slopes of G.Wilis Madiun Regency and reforestation /reforestation required for the green forest to return, flora / fauna grow and avoidedlandslides and fresh air / autoproduction.